(untitled) (Scientia Agricola, 2014)
Management systems may influence the structural quality of soils. Tensile strength (TS) and friability (F) are indicators of soil structural quality. The aim of this study was to evaluate the TS and F of an Alfisol under different management systems. The treatments were as follows: (i) soil under conventional system with growing maize after tobacco cultivation, (ii) soil under conventional system with growing maize after use as pasture, (iii) soil under natural pasture, and (iv) a natural area with predominance of spontaneous vegetation. TS and F were evaluated at depths of 0.00-0.05 and 0.05-0.10 m. The water content of soil aggregates, soil particle-size distribution, total organic carbon, carbon in the coarse fraction and carbon associated with minerals were also determined. The increase in clay content and soil organic carbon influences the values of TS. The lowest TS was for the soil under maize cultivation after tobacco in the conventional system. Soil under natural area in the 0.05-0.10 m layer was classified as slightly friable, while other systems were classified as friable. Evaluations of the structural quality of soils under management systems can be performed using TS. However, F was not efficient in detecting changes between the different management systems.